A46. Intensive Care Unit Management and Rapid Response: Provider and Patient Outcomes 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a1651
|View full text |Cite
|
Sign up to set email alerts
|

Variation In Use Of Intensive Care For Adults With Diabetic Ketoacidosis

Abstract: Objective-Intensive care unit (ICU) beds are limited, yet few guidelines exist for triage of patients to the ICU, especially patients at low-risk for mortality. The frequency with which lowrisk patients are admitted to ICUs in different hospitals is unknown. Our objective was to assess variation in use of intensive care for patients with diabetic ketoacidosis (DKA), a common condition with a low-risk of mortality.Design-Observational study using the New York State Inpatient Database (2005Database ( -2007. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recent data show that there is large variation across hospitals with regard to use of intensive care [13, 14]. For example, in a large, national study of admissions to ICUs across US Veterans Affairs hospitals, even after risk adjustment, admission rates for the ICU ranged from 1.6% to 29.5% [14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that there is large variation across hospitals with regard to use of intensive care [13, 14]. For example, in a large, national study of admissions to ICUs across US Veterans Affairs hospitals, even after risk adjustment, admission rates for the ICU ranged from 1.6% to 29.5% [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study from the U.S. Veterans Affairs health care system demonstrated that the majority of their ICU patients had a predicted mortality of less than 2% [15]. Other studies among patients with pulmonary embolism and diabetic ketoacidosis have also suggested that many hospitals overuse ICU care for these traditionally low-mortality conditions [16,17]. Reducing the number of available ICU beds should constrain ICU use and lessen the urge to expand the critical care workforce, without negatively impacting clinical outcomes.…”
Section: #2 "Many People Take No Care Of Their Money Till They Come mentioning
confidence: 99%
“…In a study of U.S. ICU utilization, rates of admission to ICU for all hospitalized patients ranged from 3 to 55% (15), and rates of ICU admission for patients with a diagnosis of diabetic ketoacidosis ranged from 0 to 100% (16). These findings suggest great heterogeneity in the patients that are cared for in U.S. ICU beds.…”
mentioning
confidence: 99%